2012
DOI: 10.1093/molbev/mss273
|View full text |Cite
|
Sign up to set email alerts
|

Good Codons, Bad Transcript: Large Reductions in Gene Expression and Fitness Arising from Synonymous Mutations in a Key Enzyme

Abstract: Biased codon usage in protein-coding genes is pervasive, whereby amino acids are largely encoded by a specific subset of possible codons. Within individual genes, codon bias is stronger at evolutionarily conserved residues, favoring codons recognized by abundant tRNAs. Although this observation suggests an overall pattern of selection for translation speed and/or accuracy, other work indicates that transcript structure or binding motifs drive codon usage. However, our understanding of codon bias evolution is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 40 publications
4
123
1
Order By: Relevance
“…fitness advantage relative to the ancestor (Fig. 1c), values that are substantially larger than any previous estimate of fitness for a synonymous mutation 3,[8][9][10][11] .…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…fitness advantage relative to the ancestor (Fig. 1c), values that are substantially larger than any previous estimate of fitness for a synonymous mutation 3,[8][9][10][11] .…”
Section: Resultscontrasting
confidence: 55%
“…Consistent with this expectation, estimates of fitness from comparative genomics suggest that synonymous sites are under weak purifying selection [13][14][15] , although a recent study suggests that up to 22% of synonymous sites in the Drosophila melanogaster genome may be under strong purifying selection 16 . Direct measures of fitness from site-directed mutagenesis studies tell a similar story: the fitness effects of synonymous mutations are almost always deleterious or, more rarely, weakly beneficial 3,[8][9][10][11] . Deleterious mutations are, by definition, subject to purifying selection, while weakly beneficial mutations are unlikely to be substituted by selection because either they cannot escape drift in small populations or, in large populations, are eliminated in competition with the relatively more abundant class of non-synonymous mutations with larger beneficial effects.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…(Shabalina et al, 2013). Bacterial experiments have shown that the use of single or rare codons could impose fitness disadvantage than using various codons for translation (Agashe et al, 2013), which explains the divergent codon usages of capsid genes in Taiwanese PiCVs.…”
Section: Divergences Driven By Positive Selectionmentioning
confidence: 99%
“…(Color figure online) researchers to address the role of chance and necessity at the molecular level? The key to resolving these prior questions is, at least in part, to assess the degree to which our system tracks or differs from experimental systems that replace genomic components with homologs obtained from other extant organisms (Acevedo-Rocha et al 2013;Agashe et al 2013;Andersson and Hughes 2009;Pena et al 2010;Urbanczyk et al 2012).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%